Assessment of Groin Application of Junctional Tourniquets in a Manikin Model. Issue 4 (27th May 2016) - Kragh, John F.; Lunati, Matthew P.; Kharod, Chetan U.; Cunningham, Cord W.; Bailey, Jeffrey A.; Stockinger, Zsolt T.; Cap, Andrew P.; Chen, Jacob; Aden, James K.; Cancio, Leopoldo C.
Abstract: Introduction: To aid in preparation of military medic trainers for a possible new curriculum in teaching junctional tourniquet use, the investigators studied the time to control hemorrhage and blood volume lost in order to provide evidence for ease of use. Hypothesis: Models of junctional tourniquet could perform differentially by blood loss, time to hemostasis, and user preference. Methods: In a laboratory experiment, 30 users controlled simulated hemorrhage from a manikin (Combat Ready Clamp [CRoC] Trainer) with three iterations each of three junctional tourniquets. There were 270 tests which included hemorrhage control (yes/no), time to hemostasis, and blood volume lost. Users also subjectively ranked tourniquet performance. Models included CRoC, Junctional Emergency Treatment Tool (JETT), and SAM Junctional Tourniquet (SJT). Time to hemostasis and total blood loss were log-transformed and analyzed using a mixed model analysis of variance (ANOVA) with the users represented as random effects and the tourniquet model used as the treatment effect. Preference scores were analyzed with ANOVA, and Tukey's honest significant difference test was used for all post-hoc pairwise comparisons. Results: All tourniquet uses were 100% effective for hemorrhage control. For blood loss, CRoC and SJT performed best with least blood loss and were significantly better than JETT; in pairwise comparison, CRoC-JETT ( P < .0001) and SJT-JETT ( P = .0085) were statistically significant in their mean difference, while CRoC-SJT ( P = .35) was not. For time to hemostasis in pairwise comparison, the CRoC had a significantly shorter time compared to JETT and SJT ( P < .0001, both comparisons); SJT-JETT was also significant ( P = .0087). In responding to the directive, "Rank the performance of the models from best to worst, " users did not prefer junctional tourniquet models differently ( P > .5, all models). Conclusion: The CRoC and SJT performed best in having least blood loss, CRoC performed best in having least time to hemostasis, and users did not differ in preference of model. Models of junctional tourniquet performed differentially by blood loss and time to hemostasis. JF Kragh Jr, MP Lunati, CU Kharod, CW Cunningham, JA Bailey, ZT Stockinger, AP Cap, J Chen, JK Aden 3d, LC Cancio .Assessment of groin application of junctional tourniquets in a manikin model .Prehosp Disaster Med .2016 ;31 (4 ):358 –363 .